The Real Determinants of Asset Sales - YANG, LIU (Journal of Finance, 2008)
ABSTRACT I develop a dynamic structural model in which a firm makes rational decisions to buy or sell assets in the presence of productivity shocks. By identifying equilibrium asset prices, the model also examines the aggregate asset sales activity over the business cycle. It shows that changes in productivity, rather than productivity levels, affect decisions: Firms with rising productivity buy assets and firms with falling productivity downsize (“rising buys falling”). As such, industries in which firms have less persistent and more volatile productivity experience greater asset reallocation. Using plant‐level data from Longitudinal Research Database (LRD), I find strong support for the model's predictions.